Application of non-invasive prenatal testing in late gestation in a pregnancy associated with intrauterine growth restriction and trisomy 22 confined placental mosaicism - Chih-Ping Chen; Chris Tsai; Ming-Huei Lin; Schu-Rern Chern; Shin-Wen Chen; Shih-Ting Lai; Wen-Lin Chen; Chen-Wen Pan; Wayseen Wang (Elsevier, 2017)
Objective: We present the application of non-invasive prenatal testing (NIPT) in late gestation in a pregnancy associated with intrauterine growth restriction (IUGR) and trisomy 22 confined placental mosaicism (CPM). Case report: A 35-year-old pregnant woman underwent chorionic villus sampling (CVS) at 12 weeks of gestation. The pregnancy was conceived by in vitro fertilization and intracytoplasmic sperm injection. CVS revealed a karyotype of 47,XY,+22 in all of 15 cultured chorionic villi cells. Array comparative genomic hybridization analysis on uncultured chorionic villi revealed a result consistent with trisomy 22. The woman underwent amniocentesis at 17 weeks of gestation. Amniocentesis revealed a karyotype of 46,XY in all 20 colonies of cultured amniocytes. Additional polymorphic DNA marker analysis excluded uniparental disomy 22. The parental karyotypes were normal. Prenatal ultrasound at 23 weeks of gestation revealed fetal retrognathia, IUGR and a calcified placenta. NIPT at 27 weeks of gestation using maternal plasma cell-free DNA analysis showed a chromosome Z-score of 5.74 for chromosome 22 (the Z-score for each pair of chromosomes is defined as "increased" if >3), indicating an abnormal placenta with trisomy 22 CPM leading to IUGR in the fetus. At 36 weeks of gestation, a 1754-g male fetus was delivered with cleft palate and imperforate anus but no other phenotypic abnormalities. The cord blood had a karyotype of 46,XY (40/40 cells), the umbilical cord had a karyotype of 47,XY,+22[9]/46,XY[31], and the placental tissues had a karyotype of 47,XY,+22[15]/46,XY[25]. Conclusion: NIPT in late gestation is useful in detection of placental abnormality associated with CPM and IUGR but a normal karyotype at amniocentesis.